Changes in Somatostatin-Like Immunoreactivity in the Sympathetic Neurons Projecting to the Prepyloric Area of the Porcine Stomach Induced by Selected Pathological Conditions - Palus, Katarzyna (Biomed Res Int, 2017)
The aim of the present study was to define changes in the expression of somatostatin (SOM) in the sympathetic perikarya innervating the porcine stomach prepyloric area during acetylsalicylic-acid-induced gastritis (ASA) and experimentally induced hyperacidity (HCL) and following partial stomach resection (RES). On day 1, the stomachs were injected with neuronal retrograde tracer Fast Blue (FB). Animals in the ASA group were given acetylsalicylic acid orally for 21 days. On the 22nd day after FB injection, partial stomach resection was performed in RES animals. On day 23, HCL animals were intragastrically given 5 ml/kg of body weight of a 0.25 M aqueous solution of hydrochloric acid. On day 28, all pigs were euthanized. Then, 14-μm thick cryostat sections of the coeliac-superior mesenteric ganglion (CSMG) complexes were processed for routine double-labelling immunofluorescence. All pathological conditions studied resulted in upregulation of SOM-like (SOM-LI) immunoreactivity (from 14.97 ± 1.57% in control group to 33.72 ± 4.39% in the ASA group, to 39.02 ± 3.65% in the RES group, and to 29.63 ± 0.85% in the HCL group). The present studies showed that altered expression of SOM occurs in sympathetic neurons supplying the prepyloric area of the porcine stomach during adaptation to various pathological insults.